ASEAN corporate governance scorecard country reports and assessments 2019. - Asian Development Bank (Manila,Philippines Asian Development Bank, 2021)
The mean total score of top publicly listed companies rated increased by 12% in 2019 compared to 2017, showing improvement in corporate governance practices. The revised ACGS comprises five parts based on the Organisation of Economic Cooperation and Developments principles: shareholders rights, equitable treatment of shareholders, stakeholders role, disclosure and transparency, and board responsibilities.
2016 Holistic Review of the ASEAN Corporate Governance Scorecard - - Overview of the Revised ASEAN Corporate Governance Scorecard - - 2019 ASEAN Corporate Governance Scorecard Awards.
Keywords: Corporate governance; Corporate governance -- Asia; Electronic book